Estimation of mortality among HIV-infected people on antiretroviral treatment in east Africa: a sampling based approach in an observational, multisite, cohort study - Geng, Elvin H; Odeny, Thomas A; Lyamuya, Rita E; Nakiwogga-Muwanga, Alice; Diero, Lameck; Bwana, Mwebesa; Muyindike, Winnie; Braitstein, Paula; Somi, Geoﬀrey R; Kambugu, Andrew; Bukusi, Elizabeth A; Wenger, Megan; et al. (The lancet HIV, 2015)
Background: Mortality in HIV-infected people after initiation of antiretroviral treatment (ART) in resource-limited settings is an important measure of the eﬀectiveness and comparative eﬀectiveness of the global public health response. Substantial loss to follow-up precludes accurate accounting of deaths and limits our understanding of eﬀectiveness. We aimed to provide a better understanding of mortality at scale and, by extension, the eﬀectiveness and comparative eﬀectiveness of public health ART treatment in east Africa. Methods: In 14 clinics in ﬁve settings in Kenya, Uganda, and Tanzania, we intensively traced a sample of patients randomly selected using a random number generator, who were infected with HIV and on ART and who were lost to follow-up (>90 days late for last scheduled visit). We incorporated the vital status outcomes for these patients into analyses of the entire clinic population through probability-weighted survival analyses. Findings: We followed 34 277 adults on ART from Mbarara and Kampala in Uganda, Eldoret, and Kisumu in Kenya, and Morogoro in Tanzania. The median age was 35 years (IQR 30–42), 11 628 (34%) were men, and median CD4 count count before therapy was 154 cells per μL (IQR 70–234). 5780 patients (17%) were lost to follow-up, 991 (17%) were selected for tracing between June 10, 2011, and Aug 27, 2012, and vital status was ascertained for 860 (87%). With incorporation of outcomes from the patients lost to follow-up, estimated 3-year mortality increased from 3·9% (95% CI 3·6–4·2) to 12·5% (11·8–13·3). The sample-corrected, unadjusted 3-year mortality across settings was lowest in Mbarara (7·2%) and highest in Morogoro (23·6%). After adjustment for age, sex, CD4 count before therapy, and WHO stage, the sample-corrected hazard ratio comparing the settings with highest and lowest mortalities was 2·2 (95% CI 1·5–3·4) and the risk diﬀerence for death at 3 years was 11% (95% CI 5·0–17·7). Interpretation: A sampling-based approach is widely feasible and important to an understanding of mortality after initiation of ART. After adjustment for measured biological drivers, mortality diﬀers substantially across settings despite delivery of a similar clinical package of treatment. Implementation research to understand the systems, community, and patients’ behaviours driving these diﬀerences is urgently needed.
Keywords: Mortality; HIV; Antiretroviral treatment; East Africa